2008
DOI: 10.1016/j.jpaa.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Pointlike sets with respect to R and J

Abstract: We present an algorithm to compute the pointlike subsets of a finite semigroup with respect to the pseudovariety R of all finite R-trivial semigroups. The algorithm is inspired by Henckell's algorithm for computing the pointlike subsets with respect to the pseudovariety of all finite aperiodic semigroups. We also give an algorithm to compute J-pointlike sets, where J denotes the pseudovariety of all finite J-trivial semigroups. We finally show that, in contrast with the situation for R, the natural adaptation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…An ℓ-template is said to be unambiguous if all pairs t i , t i+1 are either two letters, two incomparable sets or a set and a letter that is not included in the set. We now use p-implementations to prove (1) =⇒ (2). The proof is divided in two steps.…”
Section: Separation By Piecewise Testable Languagesmentioning
confidence: 99%
See 1 more Smart Citation
“…An ℓ-template is said to be unambiguous if all pairs t i , t i+1 are either two letters, two incomparable sets or a set and a letter that is not included in the set. We now use p-implementations to prove (1) =⇒ (2). The proof is divided in two steps.…”
Section: Separation By Piecewise Testable Languagesmentioning
confidence: 99%
“…In the case that disjoint elements of C cannot always be separated by an element of Sep, several natural questions arise: (1) given elements L 1 , L 2 in C, can we decide whether a separator exists in Sep? (2) if so, what is the complexity of this decision problem? (3) can we, in addition, compute a separator, and what is the complexity?…”
Section: Introductionmentioning
confidence: 99%
“…Almeida [3] established a connection between a number of separation problems and properties of families of monoids called pseudovarieties. Almeida shows, e.g., that deciding whether two given regular languages can be separated by a language with its syntactic monoid lying in pseudovariety V is algorithmically equivalent to computing two-pointlike sets for a monoid in pseudovariety V. It is then shown by Almeida et al [4] how to compute these two-pointlike sets in the pseudovariety J corresponding to piecewise testable languages. Henckell et al [12] and Steinberg [25] show that the two-pointlike sets can be computed for pseudovarieties corresponding to languages definable in first order logic and languages of dot depth at most one, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…so that q 2 m L R q 2 m L b, and by Lemma 4.5 (5), q 2 m L b = q 2 m L . Thus, choosing t := m L gives q 1 t = q 1 b and q 2 t = q 2 m L b.…”
Section: A Is An H-automatonmentioning
confidence: 87%
“…There has been a great deal of work on pointlike sets and there are many decidability results. A by no means exhaustive list of examples include: J [30,9], R (the variety of R-trivial semigroups) [5], any decidable variety of finite abelian groups [13], the variety of finite p-groups for a prime p [31] and the variety of finite nilpotent groups [1]. Also if V is a variety of finite monoids with decidable pointlikes, then the second author showed that V * D has decidable pointlikes, where * is the semidirect product of varieties and D is the variety of finite semigroups whose idempotents are right zeroes.…”
Section: Introductionmentioning
confidence: 99%